Recruitment of Persons with Disabilities (PWD): a Systematic Literature Review - Muhammad Ersan Pamungkas; Mala Sondang Silitonga (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2026)
This study provides a systematic literature review examining the recruitment of persons with disabilities (PWD) across diverse national and organizational settings. It synthesizes theoretical developments from the medical, social, human rights, and capability models of disability, critically interrogating how these inform both policy and practice in recruitment and workplace inclusion. Drawing from recent empirical studies–2025), the review identifies persistent challenges, such as legal-practice gaps, attitudinal biases, inaccessible systems, and intersectional disadvantages experienced by PWD—while also highlighting emerging evidence-based strategies like inclusive recruitment frameworks, reasonable accommodations, and multi-level policy reforms that foster equitable labor market access. The article underscores that genuine inclusion demands coordinated action from policymakers and organizations, rigorous measurement of outcomes, and intersectional, context-driven approaches rooted in justice and human rights. Ultimately, it concludes that recruiting PWD is not only a legal and ethical imperative but also a strategy for organizational excellence, innovation, and sustainable, inclusive growth.